Replication of functional serotonin receptor type 3A and B variants in bipolar affective disorder: a European multicenter study - Hammer, Christian; Röth, Ralph; Rappold, Gudrun; Rietschel, Marcella; Niesler, Beate (Translational Psychiatry, 2012)
Serotonin type 3 receptors (5-HT3) are involved in learning, cognition and emotion, and have been implicated in various psychiatric phenotypes. However, their contribution to the pathomechanism of these disorders remains elusive. Three single nucleotide polymorphisms (SNPs) in the HTR3A and HTR3B genes (rs1062613, rs1176744 and rs3831455) have been associated with bipolar affective disorder (BPAD) in pilot studies, and all of them are of functional relevance. We performed a European multicenter study to confirm previous results and provide further evidence for the relevance of these SNPs to the etiology of neuropsychiatric disorders. This involved analysis of the distribution of the three SNPs among 1804 BPAD cases and 2407 healthy controls. A meta-analysis revealed a pooled odds ratio of 0.881 (P=0.009, 95% confidence intervals=0.802-0.968) for the non-synonymous functional SNP HTR3B p.Y129S (rs1176744), thereby confirming previous findings. In line with this, the three genome-wide association study samples BOMA (Bonn-Mannheim)-BPAD, WTCCC (Wellcome Trust Case Control Consortium)-BPAD and GAIN (Genetic Association Information Network)-BPAD, including >3500 patients and 5200 controls in total, showed an overrepresentation of the p.Y129 in patients. Remarkably, the meta-analysis revealed a P-value of 0.048 (OR=0.934, fixed effect model). We also performed expression analyses to gain further insights into the distribution of HTR3A and HTR3B mRNA in the human brain. HTR3A and HTR3B were detected in all investigated brain tissues with the exception of the cerebellum, and large differences in the A:B subunit ratio were observed. Interestingly, expression of the B subunit was most prominent in the brain stem, amygdalae and frontal cortex, regions of relevance to psychiatric disorders. In conclusion, the present study provides further evidence for the presence of impaired 5-HT3 receptor function in BPAD.